Polyanions decelerate the kinetics of positively charged gramicidin channels as shown by sensitized photoinactivation. - Antonenko, Yuri N (2002)
The effects of different anionic polymers on the kinetic properties of ionic channels formed by neutral gramicidin A (gA) and its positively charged analogs gramicidin-tris(2-aminoethyl)amine (gram-TAEA) and gramicidin-ethylenediamine (gram-EDA) in a bilayer lipid membrane were studied using a method of sensitized photoinactivation. The addition of Konig's polyanion caused substantial deceleration of the photoinactivation kinetics of gram-TAEA channels, which expose three positive charges to the aqueous phase at both sides of the membrane. In contrast, channels formed of gram-EDA, which exposes one positive charge, and neutral gA channels were insensitive to Konig's polyanion. The effect strongly depended on the nature of the polyanion added, namely: DNA, RNA, polyacrylic acid, and polyglutamic acid were inactive, whereas modified polyacrylic acid induced deceleration of the channel kinetics at high concentrations. In addition, DNA was able to prevent the action of Konig's polyanion. In single-channel experiments, the addition of Konig's polyanion resulted in the appearance of long-lived gram-TAEA channels. The deceleration of the gram-TAEA channel kinetics was ascribed to electrostatic interaction of the polyanion with gram-TAEA that reduces the mobility of gram-TAEA monomers and dimers in the membrane via clustering of channels.